Clinical outcomes associated with left atrial appendage occlusion via implanted device in atrial fibrillation:a Nationwide Matched Control Study. (19th May 2022) - Maille, B; Defaye, P; Herber, J; Clerc, JM; Cuzol, F; Deharo, JC; Fauchier, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction / Background: Left atrial appendage occlusion (LAAO) has emerged as a nonpharmacological alternative for stroke prevention in patients with atrial fibrillation (AF). Contemporary data regarding the characteristics and outcomes of patients undergoing this procedure compared to a control group not treated with LAAO are limited. Purpose: Our objective was to compare outcomes following first LAAO implantation in an exhaustive nationwide matched cohort. Methods: This French longitudinal cohort study was based on the national hospitalization database covering hospital care from for the entire population. All adults (age ≥18 years) hospitalized in French hospitals with AF from January 1, 2015 to January 1, 2020, who underwent a LAAO implantation were identified. Owing to the non-randomized nature of the study, and considering for significant differences in baseline characteristics between AF patients treated with LAAO and no LAAO, propensity-score matching was used to control for potential confounders of the treatment outcome relationship. The primary outcome was a composite of ischemic stroke, major bleeding (Bleeding Academic Research Consortium ≥3) or all-cause mortality during follow-up. Results: After propensity score matching 2, 682 patients with LAAO were matched 1:1 with 2, 682 AF patients not treated with LAAO. Baseline characteristics of matched patients are illustrated in Figure 1. Mean follow-up was 7 months (median 5, interquartile 1-11 months). As illustrated in Figure 2, AF patients treated with LAAO had a significantly lower risk of the primary composite outcome as compared with patients not treated with LAAO (hazard ratio [HR] 0.59, 95% confidence interval [CI]: 0.52 to 0.68). Total events and event rates per 100 patient-years were (LAAO vs. no LAAO) 315 vs. 591 and 20.6%/year vs. 36.1%/year, respectively. The risk of ischemic stroke was comparable between groups (HR 1.06, 95% CI: 0.75 to 1.17), while risk of major bleeding (HR 0.49, 95% CI: 0.37 to 0.65) and all-cause mortality (HR 0.57, 95% CI: 0.48 to 0.67) were significantly lower in patients treated with LAAO. Conclusion: Among AF patients with a high risk of bleeding, our nationwide study highlighted a high risk of clinical events during follow-up. Patients treated with LAAO may have similar stroke prevention efficacy but lower risk of major bleeding and mortality when compared to propensity score-matched patients not treated with LAAO.